Linfadenectomia inguinal vídeo endoscópica: modificação da técnica para tratamento minimamente invasivo das metástases inguinais do câncer de pênis - NASCIMENTO, Francisco Sérgio Moura Silva do (2025)
Penile cancer (PCa) is a rare neoplasm in developed countries, but has a high incidence in developing nations, such as Brazil. Spread to inguinal lymph nodes is a critical factor in disease progression and patient prognosis. Inguinal lymphadenectomy, surgical removal of affected lymph nodes, is the treatment of choice in these cases. This cross-sectional study was conducted with patients diagnosed with PCa treated at the University Hospital of UFMA, who underwent penectomy followed by open and video endoscopic inguinal lymphadenectomy (VEIL) between 2018 and 2024. Demographic and clinical characteristics of patients undergoing both types of lymphadenectomy were collected for comparison between groups. The analysis included surgery time, days of hospitalization, number of isolated and affected lymph nodes, postoperative output, and complications. Statistical analysis was performed using means, medians, and 95% confidence intervals. When comparing the open approach with the VEIL, the mean surgery time was longer in the VEIL group (275.58 minutes) compared to the group with the open technique (199.10 minutes), but the length of hospital stay was significantly shorter in the VEIL group (5 days vs. 16 days, p < 0.001). Patients treated with VEIL had a lower mean number of isolated lymph nodes (6.50) compared to the open technique (10.50), and also had fewer affected lymph nodes (median 0 vs. 2, p < 0.001). Severe postoperative complications were less frequent in the VEIL group, with a lower incidence of skin flap necrosis (2% VEIL vs. 40% open, p < 0.001) and dehiscence (0% VEIL vs. 30% open, p < 0.001). We conclude that video-endoscopic inguinal lymphadenectomy demonstrated a significant reduction in postoperative morbidity, with shorter hospital stay and lower incidence of serious complications, when compared to the open approach.